A hedging policy for carriers' selection under availability and demand uncertainty. (January 2016) - Feki, Yassin; Hajji, Adnène; Rekik, Monia
Highlights: We address operational carrier selection in dynamic stochastic contexts. Both demand and carriers' availability are dynamic stochastic. Optimal control theory concepts are adapted to the carriers' selection problem. Three thresholds of the available inventory in the depot govern the carriers' selection policy. The proposed policy outperforms two other carrier selection policies. Abstract: We address a stochastic dynamic distribution problem where a family of products needs to be shipped from a warehouse to a distribution center (DC). Uncertainty is on carriers' availability and demand at the DC. Internal, external and spot carriers must be optimally selected to minimize the expected discounted cost of transportation, inventories and shortages. We numerically prove that an optimal selection policy, SDMBSP, is based on three thresholds of the available inventory in the DC. A simulation model is proposed and proves the robustness of the SDMBSP and its outperformance over two other carrier selection policies.